Structural modification and dynamic in vitro fermentation profiles of precooked pea starch as affected by different drying methods. Issue 24 (30th November 2021) - Chang, Danni; Ma, Zhen; Li, Xiaoping; Hu, Xinzhong
Abstract : Pea starch was pre-cooked before being subjected to different drying treatments including oven-drying, infrared-drying, microwave-drying and freeze-drying. Abstract : Pea starch was pre-cooked before being subjected to different drying treatments including oven-drying, infrared-drying, microwave-drying and freeze-drying. Different dried pea starch samples were then anaerobically fermented by human gut microbiota. Their structural features, morphological changes, the synthesis of short-chain fatty acids, as well as the microbiological responses during the 24 h in vitro human fecal fermentation were determined. Oven-dried pea starch (ODPS) displayed relatively stronger fluorescence intensity on the confocal laser scanning microscopic images, which was in qualitative agreement with its significantly highest crystallinities obtained from X-ray diffractogram (XRD) and 13 C cross-polarization magic angle spinning ( 13 C CP/MAS) NMR. The obtained results demonstrated that the significant differences in structural and morphological features observed for these four dried starch samples originate from different evaporation patterns of water molecules. Changes in R 1047/1022 and R 995/1022 during in vitro colonic fermentation corresponded well with the transition in relative crystallinity obtained from XRD and 13 C CP/MAS NMR measurements, suggesting an increase in the molecular order upon starch utilization by the gut bacteria. The correlation analysis indicated that the dried starch with higher degree of short-range ordered structure was beneficial for the growth of Firmicutes, whereas starch substrate with a relatively loose granular structure would be beneficial for the growth of Bacteroides. The significantly highest operational taxonomic unit level of Bifidobacterium species after the fermentation of ODPS corresponded well with its highest propionate and butyrate concentration. The results obtained are expected to help food processors to tailor the drying method during the manufacture of processed starch samples with desirable structural features and prebiotic properties.